Under-mask beard covers achieve an adequate seal with tight-fitting disposable respirators using quantitative fit testing. (October 2022) - Bhatia, D.D.S.; Bhatia, K.S.; Saluja, T.; Saluja, A.P.S.; Thind, A.; Bamra, A.; Singh, G.; Singh, N.; Clezy, K.; Dempsey, K.; Hudson, B.; Jain, S.
Summary: Background: Tight-fitting respirators are a critical component of respiratory protection against airborne diseases for health workers. However, they are not recommended for health workers with facial hair. Some health workers are unable to shave for religious or medical reasons. Under-mask beard covers have been proposed as a solution to allow health workers with facial hair to wear tight-fitting respirators. However, studies to date have been limited by their predominant reliance on qualitative rather than quantitative fit testing techniques. Aim: To assess the efficacy of under-mask beard covers in achieving an adequate seal with tight-fitting disposable P2/N95 respirators using quantitative fit testing. Methods: Bearded adult males underwent quantitative fit testing with an under-mask beard cover using either a TSI PortaCount Respirator Fit Tester 8038 or an AccuFit 9000 PRO fit testing device on up to five disposable P2/N95 respirators (3M 1860, 3M 1870+, BYD N95 Healthcare Particulate Respirator, BSN Medical ProShield N-95 Medium and Trident RTCFFP2). The primary outcome was the proportion of subjects that passed or failed quantitative fit testing with an under-mask beard cover. Findings: Thirty subjects were assessed; of these, 24 (80%) passed quantitative fit testing with at least one tight-fitting P2/N95 disposable respirator. Among these subjects, the median best-achieved fit factor was 200 (interquartile range 178–200). None of the subjects had an adverse reaction to the under-mask beard cover. Conclusion: The under-mask beard cover technique may be used to achieve a satisfactory seal with tight-fitting P2/N95 respirators in health workers with facial hair who cannot shave.